Helquats, helical extended diquats, as fast electron transfer systems - Pospísil, Lubomír; Teplý, Filip; Gál, Miroslav; Adriaenssens, Louis; Horácek, Michal; Severa, Lukás (Physical chemistry chemical physics, 2010)
Helicene-viologen structural hybrids, like [5]helquat, 6,7,10,11-tetrahydrodipyrido[2,1-a:1',2'-k][2,9]phenanthrolinediium, and its four methylated derivatives, are characterized by electrochemical admittance and EPR spectroscopy. All compounds are reversibly reduced in two one-electron steps. Formal redox potentials correlate with the calculated LUMO energies. The electron transfer is coupled with a weak adsorption of the reactants. The analysis of the frequency dependence of the electrode admittance is used for the separation of Faradaic and double layer contributions and finally to the estimation of heterogeneous rate constants. Heterogeneous rate constants determined this way are in the range 0.1 to 3 cm s(-1). In all cases the second electron transfer is faster than the first redox step by a factor of three. The Frumkin correction for the acceleration by the double layer potential further amplifies this difference. The heterogeneous rate constants of derivatives correlate with the solvent reorganization energy estimated from the Marcus model. EPR spectra confirm the radical cation formation. The radical of [5]helquat participates in an extremely fast self-exchange process with the parent dication characterized by the self-exchange rate constant k(ET) = (2.4 +/- 0.5) x 10(9) M(-1) s(-1).